An industrial Internet of things based platform for context-aware information services in manufacturing. Issue 11 (2nd November 2018) - Alexopoulos, Kosmas; Sipsas, Konstantinos; Xanthakis, Evangelos; Makris, Sotiris; Mourtzis, Dimitris
ABSTRACT: In a manufacturing shop floor, context-aware intelligent service systems can be used to provide information services to shop floor personnel, according to their situation. This article presents an industrial Internet of things (IIoT) context-aware information system that provides decision support for mobile or static operators and supervisors. The system uniquely combines key IIoT concepts such as multi-layered, service-oriented architecture, which integrates several subsystems, such as sensor data acquisition together with concepts for developing context-aware systems such as context modelling and contextual data information provision. The proposed solution is relevant for several manufacturing environments. However, in dynamic, semi-structured manufacturing environments that the workstations are not fixed but dynamically change over time and in which the workers are mobile and not static to some predefined workstations, the utilisation of context-aware information delivery is considered as even more relevant. For that reason, a case study with a medium-sized shipyard has been selected and conducted. Industrial requirements were gathered and led to use cases for a customised implementation of the proposed solution into a shipyard. The proposed solution includes a number of context-aware apps that support the users in carrying out production tasks. The study provided insights into the suitability of the solution presented in the shipyard environment and brought to light further aspects that would improve the proposed context-aware system.